LATE PLIOCENE SEDIMENTATION IN LAKE BAIKAL: IMPLICATIONS FOR CLIMATIC AND TECTONIC CHANGE IN SE SIBERIA - Müller J.; Oberhänsli H.; Melles M.; Schwab M.J. (My University, 2001)
Within the framework of the Baikal Drilling Project (BDP), a 192 m long sediment core (BDP-96-1) was recovered from the Academician Ridge, a submerged topographic high between the North and Central Basins of Lake Baikal. Sedimentological, clay mineralogical and geochemical investigations were carried out on the core interval between 90 and 124 m depth, corresponding to ca. 2.4–3.4 Ma. The aim was to reconstruct the climatic and tectonic history of the continental region during the intensification of Northern Hemisphere glaciation in Late Pliocene time. A major climate change occurred in the Lake Baikal area at about 2.65 Ma. Enhanced physical weathering in the catchment, mirrored in the illite to smectite ratio, and temporarily reduced bioproduction in the lake, reflected by the diatom abundance, evidence a change towards a colder and more arid climate, probably associated with an intensification of the Siberian High. In addition, the coincident onset of distinct fluctuations in these parameters and in the Zr/Al ratio suggests the beginning of the Late Cenozoic high amplitude climate cycles at about 2.65 Ma. Fluctuations in the Zr/Al ratio are traced back to changes in the aeolian input, with high values in warmer, more humid phases due to a weaker Siberian High. Assuming that the sand content in the sediment reflects tectonic pulses, the Lake Baikal area was tectonically active during the entire investigated period, but in particular around 2.65 Ma. Tectonic movements have likely led to a gradual catchment change since about 3.15 Ma from the western towards the eastern lake surroundings, as indicated in the geochemistry and clay mineralogy of the sediments. The strong coincidence between tectonic and climatic changes in the Baikal area hints at the Himalayan uplift being one of the triggers for the Northern Hemisphere Glaciation.
Keywords: Pliocene; Baikal; sedimentation; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен